Social conflict in the relationship between donors and beneficiaries: An analysis of Lewis Coser's Theory - Hassan, Alfi Lizan (Priviet Social Sciences Journal, 2025)
This study explores a digital philanthropic conflict between a donor and a recipient that emerged due to differing expectations regarding the use of collected donation funds. This case reflects broader structural tensions in donor-recipient relationships, particularly concerning transparency, control, and autonomy. Adopting a qualitative descriptive approach with a secondary case study method, this research draws from online media documentation and analyzes the conflict using Lewis Coser’s theory of social conflict. The analysis focuses on the functions of conflict in clarifying social boundaries, strengthening internal group solidarity, and enabling normative transformations. The findings reveal that such conflicts function not only as manifestations of interpersonal disagreement, but also as catalysts for social reflection, role renegotiation, and the redefinition of ethical expectations in charitable practices. In digital spaces, these tensions are amplified through public discourse, resulting in stronger group polarization and the solidification of collective identities. Theoretically, this study contributes to sociological debates on the constructive role of conflict in maintaining social order and cohesion. Practically, this highlights the urgent need for clearer ethical standards and mutual accountability in digital donation systems. These insights deepen the current understanding of how online philanthropy operates within the mediated public sphere and its implications for evolving civil societal norms.